Extraction of Vitamin E Isomers from Palm Oil: Methodology, Characterization, and in Vitro Anti‐Tumor Activity. (3rd August 2017) - Abu‐Fayyad, Ahmed; Nazzal, Sami
Abstract: Vitamin E refers to a family of eight tocopherols (T) and tocotrienol (T3) isomers. Due to the unique pharmacological and anticancer activity of the individual isomers, there is a need to extract and separate the individual T3 isomers from T/T3 rich fractions of palm oil. The objective of the present study was to present a detailed protocol for the extraction of gram quantities of vitamin E isomers from a T3 rich fraction (Tocotrol™) that was obtained from palm oil, by column chromatography using a binary hexane:EtOAc (1–12%) phase system. The chemical integrity and identity of the extracted isomers was confirmed by TLC, HPLC, 1 H‐NMR, and Raman analysis. To evaluate their anticancer activity, vitamin E isomers were first entrapped into nanoemulsions and then tested against a panel of breast and pancreatic cancer cell lines. Nanoemulsions were prepared by the solvent evaporation technique. They had an average droplet size between 156–200 nm. In confirmation to what has been reported in the literature, γ‐T3 and δ‐T3 isomers were found to be significantly more active against tumor cells than the α‐T and α‐T3 isomers. The current study has demonstrated the feasibility of extracting the individual vitamin E isomers at high yields from natural sources while maintaining their chemical integrity and pharmacological activity.